Detection of preperimetric glaucoma using Bruch membrane opening, neural canal and posterior pole asymmetry analysis of optical coherence tomography - Hua, Rui (Sci Rep, 2016)
We analysed retinal nerve fibre layer (RNFL) defects in eyes with normal circumpapillary RNFL (cpRNFL) thickness using posterior pole asymmetry analysis (PPAA) and investigated the parameters of Bruch membrane opening (BMO) and neural canals using enhanced depth imaging spectral domain optical coherence tomography (EDI-SDOCT). A total of 112 preperimetric glaucomatous eyes of 92 patients were examined to obtain cpRNFL thickness using SD-OCT. Posterior pole asymmetry analysis (PPAA) and central cross-sectional images of the optic nerve head (ONH) were obtained using EDI-SDOCT. Minimal and horizontal distances between the BMO and ONH surfaces (BMOM, BMOH) and the terminal of retinal pigment epithelium (RPE) and ONH surfaces (RPEM, RPEH) were measured. The distribution of the absolute black cells in PPAA was more concentrated in eyes with “U”-shaped neural canals (p < 0.0001). The area under the receiver operating characteristic curve of the ratio of RPEM to RPEH (RPE-R, 0.771 ± 0.08) was significantly larger than the ratio of BMOM to BMOH (BMO-R, 0.719 ± 0.009) for PPAA results. A U-shaped neural canal, lower ratio of RPEM to RPEH, and lower ratio of BMOM to BMOH were considered early indicators of RNFL defects in preperimetric glaucomatous eyes with normal cpRNFL.